Spatial Analysis of Digital Transformation on Food Security in Sumatra: Amidst Climate Change - Fajri, Moh Najikhul; Pratama, Backtiar Putra; Wulandari, Fifi Amilia (Jurnal Ilmu Ekonomi Terapan, 2025)
This study aims to analyze the impact of digital transformation on food security in Sumatra. The research utilizes panel data from 154 districts and cities covering the period from 2019 to 2022. Food security levels are measured using the entropy method, while the effects of digital transformation are assessed through spatial panel regression to capture both spatial and temporal variations.The results indicate that digitalization has a significant positive effect on food security in the long run. This suggests that advancements in digital technology contribute to improving food systems, enhancing distribution efficiency, and increasing access to food resources. On the other hand, fiscal decentralization policies are found to have a significant negative effect on food security, implying that disparities in regional governance capabilities may hinder efforts to improve food security across different areas. In addition to digitalization, other factors such as electrification, industrialization, and population growth show significant positive effects on food security. Electrification facilitates better access to energy, which supports agricultural infrastructure and food storage. Industrialization boosts productivity and the development of food supply chains, while population growth, despite increasing food demand, can drive agricultural expansion and improvements in food distribution when managed effectively.Overall, this study highlights the crucial role of digital transformation in enhancing food security, while also emphasizing the need for equitable fiscal policies to reduce regional disparities in food access and availability.